MEDICINAL LUNG INJURY: CLINICAL OBSERVATION - N. A. Karoli; A. P. Rebrov; E. E. Arkhangelskaya; R. N. Steshenko; A. S. Bukia; N. V. Dvornikova (Klinicist)
Presented clinical case is a classical version of «amiodarone lung» in patient taking inadequate doses of the drug, probably, according to the scenario of acute clinical course